O GÊNERO “DEFESA DA LITERATURA” NA CRÍTICA LITERÁRIA CONTEMPORÂNEA - PAIVA, Géssica Ávila dos Reis (2020)
This Dissertation proposes to analyze the texts of Tzvetan Todorov, Antonio Candido and Antoine Compagnon, on the assumption the hypothesis that they belong to a genre of literary criticism that we are calling “defense of literature” (inspired not only by the titles, but also in the arguments developed by Sidney and Shelley in their respective defenses, in the 15th and 18th centuries), since the arguments of the critics chosen to be the object of our study demonstrate that they were used in order to “defend” the place of literature in today's society , based on highlighting its attributes, its history and the fact that it has principles that activate personal, social and ethical values; contributing to the absorption of knowledge that concerns the individual and the other, in a coexistence of acceptance and respect. Among our interests during the analysis would be to establish a historical overview of the social place of literature and its decentralization, in contemporary times, since one of the argumentative regularities of the critics concerns the identification of crisis in that social place. By reason of the texts belonging to the corpus present argumentative convergences, in several thematic axes, we use Mikhail Bakhtin theoretical references to direct the paths of this verification regarding the genre “defense of literature”, so that our inclination, taking as a basis the results, it is in the sense that there are among the texts of the critics mentioned, compound arguments with similar communicative purposes, as well as a concern, in the structuring of their ideas, with the purpose of legitimizing literature for society, being characterized as a genre contemporary literary criticism itself.